COVID-19 DAN KEKERASAN SIMBOLIK - M Yusuf, Syahril (Al-Ijtima`i: International Journal of Government and Social Science, 2021)
The new virus is now known as the corona virus. Corona virus is a virus that attacks the respiratory system. A disease due to viral infection is called COVID-19. The majority of cases there is a corona virus in Wuhan, China. In March 2020, the World Health Organization (WHO) announced the corona virus as a pandemic. Pandemic COVID-19 becomes much discussed worldwide. This study aims to look at the impact of social phenomenon with the presence of the corona virus through various media; both print and electronic that led to symbolic violence. The results showed that the symbolic violence is present in a variety of ways with specific objectives.